Graduate Programs in Green Growth and Sustainable Development: A Comparative Approach - Alan Fairlie Reinoso (Pontificia Universidad Católica del Perú, 2017)
Since the concern about the negative impacts of the current economic model in the scarcity of natural resources and their conservation, it comes the need to confront them and create, from academia, some research areas that include these new features and development trends. In this paper, an overview of the conceptual aspects of the main proposals for the transition to sustainable development is performed, such as the Green Growth, Bio-Commerce, Bio-Economy, among others. Then, it is identified and analyzed a group of graduate programs developed on the sustainable development. Finally, a comparative balance, based on the offer of the Master of Bio and Sustainable Development.